Review on Nexus between Economic Growth and Environmental Quality - A/L Ramakrishna, Suresh; Ahmad, Humara; Imran Qureshi , Muhammad; Khan, Nohman (International Journal of Psychosocial Rehabilitation, 2020)
Environmental quality is the most important issue to be discussed now days. The emerging Asian countries are passing through the phase of economic transformation from agriculture to industrialization. Economic development is considered the main cause of increase in pollution so it is assumed that pollution is the bi-product of development. The evolution of Environmental Kuznets curve theory was the debate between the growth and environmental quality. The massive economic growth is the cause of excessive utilization of resources that is the reason of bio diversity loss. The objective of the current study is to check the presence of EKC in emerging Asian countries. The presences of Environmental Kuznets curve will roll out the problem that either increasing rate of growth will affect the environmental quality or not?